Channel-Length-Modulated Avalanche Multiplication in Ambipolar WSe2 Field-Effect Transistors - Jaeyoung Kim; Kyungjune, Cho; Jinsu Pak; Woocheol Lee; Junseok Seo; Jae-Keun Kim; Jiwon Shin; Juntae Jang; Kyeong-Yoon Baek; Jonghoon LeeJonghoon Lee; Chung, Seung jun; Keehoon Kang; et al. (American Chemical Society, 2022)
Recently there has been growing interest in avalanche multiplication in two-dimensional (2D) materials and device applications such as avalanche photodetectors and transistors. Previous studies have mainly utilized unipolar semiconductors as the active material and focused on developing high-performance devices. However, fundamental analysis of the multiplication process, particularly in ambipolar materials, is required to establish high-performance electronic devices and emerging architectures. Although ambipolar 2D materials have the advantage of facile carrier-type tuning through electrostatic gating, simultaneously allowing both carrier types in a single channel poses an inherent difficulty in analyzing their individual contributions to avalanche multiplication. In ambipolar field-effect transistors (FETs), two phenomena of ambipolar transport and avalanche multiplication can occur, and both exhibit secondary rise of output current at high lateral voltage. We distinguished these two competing phenomena using the method of channel length modulation and successfully analyzed the properties of electron- and hole-initiated multiplication in ambipolar WSe2 FETs. Our study provides a simple and robust method to examine carrier multiplication in ambipolar materials and will foster the development of high-performance atomically thin electronic devices utilizing avalanche multiplication.